Educational Innovation in the Era of the Fourth Industrial Revolution to Enhance Global Competitiveness - Nurbuana, Nurbuana; Sirozi, Muhammad (FKIP - Universitas Riau, 2025)
The Fourth Industrial Revolution has brought significant transformations across various sectors, including education. These changes demand a comprehensive reform in the educational system to produce competent, adaptive, and globally competitive human resources. This study aims to explore relevant and effective educational innovations to enhance graduates’ global competitiveness in the digital era. The method employed is a library research approach, involving the collection, review, and analysis of scholarly literature related to educational innovation, technology integration, and contemporary learning strategies. The findings indicate that educational innovation spans various dimensions, including pedagogical approaches such as project-based learning, flipped classrooms, collaborative learning, and the integration of technologies such as Augmented Reality (AR) and Virtual Reality (VR). Moreover, innovations extend to evaluation systems, school management, and administrative strategies to foster effective and contextual learning environments. These innovations have been shown to improve student engagement, strengthen conceptual understanding, and support the development of 21st-century competencies. The study concludes that educational innovation is a strategic imperative for addressing the challenges of the Fourth Industrial Revolution. It calls for synergy among all educational stakeholders to realize sustainable transformation, with a focus on developing globally oriented competencies and an educational system that is responsive to ongoing societal changes.